2017
DOI: 10.9734/arjass/2017/32605
|View full text |Cite
|
Sign up to set email alerts
|

Investigating the Impact of Oil Export on Gross Capital Formation in Nigeria

Abstract: This study examined impact of oil export on gross capital formation in Nigeria for the period of 1980-2015. The study specified the model as gross capital formation (GCF) being a function of oil export (OEX), real gross domestic product (RGDP) and exchange rate. The pre test carried out in the study are unit root test and co integration test while VECM econometric test was used to test the impact of the explanatory variables on the dependent variable. Based on the above stated econometric procedure, the study … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
3
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 2 publications
(3 reference statements)
0
3
0
Order By: Relevance
“…But one of the major factor needs to be noted that such oil booms are channelizing investment towards in oil production and extraction related areas, this leading to “resource movement effect” proposed by Corden and Neary (1982). We are accepting the above results by strongly contradicting the findings of Chinyere et al (2017) as it quotes that oil exports are inversely related to gross capital formation.…”
Section: Empirical Analysismentioning
confidence: 74%
See 1 more Smart Citation
“…But one of the major factor needs to be noted that such oil booms are channelizing investment towards in oil production and extraction related areas, this leading to “resource movement effect” proposed by Corden and Neary (1982). We are accepting the above results by strongly contradicting the findings of Chinyere et al (2017) as it quotes that oil exports are inversely related to gross capital formation.…”
Section: Empirical Analysismentioning
confidence: 74%
“…It is implicitly suggested that encouraging non-oil export activities can stimulate long-term economic growth. Chinyere et al (2017) state that oil export inversely and significantly impacts gross capital formation in Nigeria both in long run and short run. The above studies strongly opposing the theoretical framework suggested by Corden and Neary (1982) for resource endowed economies.…”
Section: Literature Reviewmentioning
confidence: 99%
“…This study is one that is closer to the present study because it gave attention to an aspect of globalization which is trade. Ozuzu and Ewubare [26] extending the study by Udude et al [27] also investigated the impact of export earnings on capital formation in Nigeria. Data analysis was done using OLS technique.…”
Section: Import/export and Capital Formationmentioning
confidence: 99%
“…In examining the impact of oil export on gross capital formation in Nigeria from 1980 to 2015, Udude et al [20] developed a model using the VECM technique. Their result showed that oil export inversely and significantly impacts gross capital formation in Nigeria in short run and long run within the period under review.…”
Section: Luckymentioning
confidence: 99%